2009
DOI: 10.1136/jnnp.2009.183665
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GM1 IgG antibodies in Guillain-Barre syndrome: fine specificity is associated with disease severity

Abstract: Differences in fine specificity of antibodies are strong indications that different regions of the GM(1)-oligosaccharide are involved in antibody binding. High titres of specific anti-GM(1) antibody binding to cellular GM(1) can be explained by antigen exposure, that is, GM(1) exposes or forms mainly epitopes recognised by specific antibodies, and 'hides' those involved in binding of cross-reacting antibodies. Thus, the fine specificity of anti-GM(1) antibodies may influence disease severity by affecting antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Removal of autoantibodies, by PE, creates a concentration gradient between the lowered blood level and the extravascular space forcing antibody movement from the extra to the intra vascular space to be removed during the subsequent session [40]. Specific anti-ganglioside antibody levels were recently found to be associated with disease severity [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Removal of autoantibodies, by PE, creates a concentration gradient between the lowered blood level and the extravascular space forcing antibody movement from the extra to the intra vascular space to be removed during the subsequent session [40]. Specific anti-ganglioside antibody levels were recently found to be associated with disease severity [41]. …”
Section: Discussionmentioning
confidence: 99%
“…(2,3) For example, the titers of serum anti-GM1 antibodies may reflect differences in disease severity, and possibly, different subgroups of GBS patients. (4,5) Additionally, there is evidence showing that both Th1 cell-mediated and Th2 cell-mediated responses are involved in the pathogenesis of GBS. (6) Activated T-cell mediated immunity plays an important role in autoimmune diseases, (7) and the balance between Th1 and Th2 cytokines may determine disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…More recently it was reported that rabbits, immunized with GM1 and KLH, which developed an axonal neuropathy had highaffinity antibodies, whereas the only rabbit immunized with the same procedure, which did not developed the neuropathy did not have highaffinity antibodies [18]. In support of the importance of monospecific antibodies Lardone and co-workers found significant associations between fine specificity and disease severity also in GBS patients [21].…”
Section: Discussionmentioning
confidence: 94%
“…Recently the presence of monospecific and high-affinity anti-ganglioside antibodies has been associated with the induction of experimental ataxic and axonal neuropathy in rabbits and with disease severity in human GBS [18][19][20][21]. Human GBS is associated with IgG1 and IgG3 isotypes, which need CD40l involvement.…”
Section: Introductionmentioning
confidence: 99%